Peer power : transforming workplace relationships - Clay, Cynthia, 1955- (Jossey-Bass, a Wiley Imprint, 2012)
"Developed for training, HR, and OD professionals, this book provides the keys to effective interpersonal collaboration. Building on a foundation of four principles (Be Real, Extend Respect, Take Responsibility, and Build Relationships). Readers will learn how to apply five strategies (Collaborating, Going Head-to-Head, Compromising, Coaching, and Caring-for-Self) at the moment of need (a deteriorating relationship with a coworker or boss) and discover how to win support from others and manage difficult behavior when conflict arises. They describe several familiar and troublesome 'mistakes' workmates often make, then help us avoid them by applying four essential principles and five key strategies. Features content to deepen the readers' understanding of each concept and strategy with real life examples along with questionnaires at the end of each case chapter. Peer Power tells relevant stories, gives concrete examples of solutions, and provides real tools to repair relationships with these individuals. Practicing these tools improves effectiveness, reduces stress levels, helps build our company and makes this a better place to work. Chapter 1 looks at interpersonal behaviors that most of us have tried but don't work. Chapter 2 introduces the four key principles for effective communication. Chapter 3 dives into the five strategies for solving interpersonal problems. In the nine chapters that follow, the book tackles a challenging character at work The attacker (the colleague who repeatedly expresses his anger and frustration in the form of inappropriate personal criticism) The whiner (that coworker who complains without taking responsibility for improving conditions that surround her) The scene stealer (the peer who sets about building her reputation at your expense) The drive-by boss (a leader who ignores some of his key management responsibilities and doesn't meet the needs of his employees or the organization) The manipulator (the coworker who attempts to influence your attitude or behavior through deception or secrecy) The clueless colleague (a coworker who is insensitive to her negative impact on the work environment) The faux-smart boss (the boss who has unrealistic confidence in his own ideas and skills, often accompanied by a lack of confidence in his employees) The slacker (the coworker whose poor performance damages your performance) The bully (a colleague who uses unreasonable demands and inappropriate threats to get her way) For a quick road map, readers can turn to the cheat sheet at the end of each of these chapters. Each case chapter includes clues to look for, assumptions to remember, and principles and practices to use. For actual dialogue, the authors have added scripted responses to various tough cases. The book is designed for readers to use this book to develop practical strategies to get results"--